The Effectiveness Of Health Promotion On Handwashing Behavior With Soap In School Children - Elvira Safidni; Rezqiqah Aulia Rahmat; Dia Rejeki Utami; Andrias Horhoruw (International Journal of Health Sciences, 2026)
Handwashing with soap (HWWS) is a clean and healthy lifestyle behavior that is effective in preventing various infectious diseases such as diarrhea and respiratory tract infections. School-age children are a group that is vulnerable to disease due to lack of hygiene practices. Health promotion in schools is an important strategy to improve HWWS behavior in children. This study aims to determine the effectiveness of health promotion on handwashing with soap behavior in school children. The study used a quasi-experimental design with a pretest - posttest approach. The study sample was 60 elementary school students selected using a purposive sampling technique. Data were collected through observation and questionnaires on HWWS behavior before and after health promotion. Data analysis used a paired t- test. The results showed a significant increase in HWWS behavior from an average score of 56.4 ± 9.2 to 78.6 ± 8.5 after the health promotion intervention (p < 0.001). It was concluded that health promotion is effective in improving handwashing with soap behavior in school children.